Use of the Veterans' Choice Program and Attrition From Veterans Health Administration Primary Care. Issue 12 (December 2020) - Yoon, Jean; Leung, Lucinda B.; Rubenstein, Lisa V.; Rose, Danielle E.; Stockdale, Susan E.; Kaboli, Peter J.; Chow, Adam
Abstract : Background: Concerns over timely access and waiting times for appointments in the Veterans Health Administration (VHA) spurred the push towards greater privatization. In 2014, VHA increased the provision of care from community providers through the Veterans' Choice Program (Choice). Objectives: We examined the characteristics of patients and practices more likely to use Choice care and whether using Choice care affected patients' attrition from VHA primary care. Study Design: We conducted a longitudinal study of VHA primary care users in the fiscal year 2015 and their attrition 2 years later. In the multivariate analysis, we examined whether attrition from VHA primary care was related to prior use of Choice care. Subjects: A total of 1.4 million nonelderly patients diagnosed with chronic conditions. Measures: Choice outpatient care utilization was measured in the baseline year. Attrition was measured as not receiving any VHA primary care in 2 subsequent years. Results: In our cohort, 93, 710 (7%) patients used some Choice outpatient care, and these patients were more likely to be female, White or Hispanic, to have more primary care utilization at baseline, and to have long driving distances to VHA care. Practices which sent more patients out for Choice care had lower mean scores for patient-centered medical home implementation and longer mean waiting times for appointments. In the adjusted analysis, the probability of attrition was significantly lower (−0.009) among patients who used Choice outpatient care (0.036) versus patients who did not (0.044) ( P <0.001). Conclusion: The use of community outpatient providers in the Choice program was associated with less attrition from VHA primary care.